Optimization of Strategic Policy for the Prevention and Law Enforcement of the Crime of People Smuggling - Wilda Ramadhani Mansur; Adhitya Antomarta (Polteknik Imigrasi, 2021)
People smuggling as one of the transnational crimes that threatens Indonesia is still a global problem that is still difficult to find a way out. In addressing this issue, Indonesia must adhere to the precautionary principle but still prioritize state security. This study aims to determine the practice of people smuggling in Indonesia, how to regulate criminal acts and the formulation of policies related to people smuggling in Indonesian national law. This writing uses a juridical-normative approach through collecting data and library materials relevant to the topic of this research. From the results of the study, it was found that border control policies, deportation policies and legalization policies, as well as inspection policies on work locations, raids, and strict sanctions against perpetrators of people smuggling agents need to be carried out in the context of law enforcement against people smuggling crimes. In this case, the government through immigration as the relevant agency needs to conduct a study and draft special legal rules for people smuggling in Indonesia.